Optimizing Patient Care: Interdisciplinary Collaboration and Evidence-Based Practice in Nursing and Pharmaceutical Care (Asian Journal of Pharmaceutics (AJP), 2024)
The goal of pharmaceutical care is to maximize therapeutic results and reduce any sort of medical errors byfostering interprofessional collaboration. Nurses play a very important role in medication safety and providingthe best pharmaceutical care to patients because they are often the frontliners in the healthcare system. They helpthe patient adhere to their dosage regimen and usually are the first ones who report any signs of adverse drugresponses. Moreover, using digital healthcare tools, such as electronic medication administration records (eMAR) ortelemedicine can ease inter-professional collaboration. This review analyzed case studies and literature focusing ondigital health tools, the WHO guidelines, and European Council recommendations to explore the possibilities of nursedrivenpharmaceutical care. Major aspects, such as interprofessional collaboration, evidence-based practices, andadvanced technologies, such as artificial intelligence and wearables were considered for their impact on patient care.Interprofessional collaboration improved patients’ compliance, reduced prescribing errors, and enhanced treatmentoutcomes. However, some relevant barriers were identified: deficient training, power imbalances, and communicationfailures. Some promising digital technologies include AI, wearables, and data analytics applied to address theseissues to hasten the delivery of care. Medicine can be enhanced by removing obstacles to cooperation throughmutual respect, training, and the incorporation of cutting-edge technologies. The use of digital tools and evidencebasedprocedures enables nurses to monitor and customize patient care better. Issues such as hierarchical dynamicsand lack of interprofessional education need to be addressed to encourage productive teamwork and enhance patientoutcomes. The inter-personnel collaboration has resulted in better therapeutic responses in patients and it has beenreported to reduce medication errors and thereby improve patient adherence and therapeutic results. Nurses are better equipped to monitor and customize care because of advanced technologies, such as wearables and data analytics. Safe and efficient medication management requires nurse-driven pharmaceutical care backed by interprofessional teamwork and Evidence-Based Practice. Furthermore, investing in digital technologies and cooperative training will aid in smooth collaboration and optimized pharmaceutical care.